Simultaneous laparoscopic multi-organ resection combined with colorectal cancer: Comparison with non-combined surgery - Kim, Hye Jin (Baishideng Publishing Group Co., Limited, 2012)
AIM: To access the short-term outcomes of simultaneous laparoscopic surgery combined with resection for synchronous lesions in patients with colorectal cancer. METHODS: Between March 1996 and April 2010 prospectively collected data were reviewed from 93 consecutive patients who had colorectal cancer and underwent simultaneous multiple organ resection (combined group) and 1090 patients who underwent conventional laparoscopic right hemicolectomy or laparoscopic low/anterior resection for colorectal cancer (non-combined group). In the combined group, there were nine gastric resections, three nephrectomies, nine adrenalectomies, 56 cholecystectomies, and 21 gynecologic resections. In addition, five patients underwent simultaneous laparoscopic resection for three organs. The patient demographics, intra-operative outcomes, surgical morbidity, and short-term outcomes were compared between the two groups (the combined and non-combined groups). RESULTS: There were no significant differences in the clinicopathological variables between the two groups. The operating time was significantly longer in the combined group than in the non-combined group, regardless of tumor location (laparoscopic right hemicolectomy and laparoscopic low/anterior resection groups; P = 0.048 and P < 0.001, respectively). The other intra-operative outcomes, such as the complications and open conversion rate, were similar in both groups. The rate of post-operative morbidity in the combined group was similar to the non-combined group (combined vs non-combined, 15.1% vs 13.5%, P = 0.667). Oncological safety for the colon and synchronous lesions were obtained in the combined group. CONCLUSION: Simultaneous laparoscopic multiple organ resection combined with colorectal cancer is a safe and feasible option in selected patients.